Characterization of Investigators' Approach to Translational Research: A Qualitative Study. Issue 6 (25th July 2014) - Rubio, Doris M.; Robinson, Georgeanna F.W.B.; Gilliam, Victoria A.; Primack, Brian A.; Switzer, Galen E.; Seltzer, Deborah L.; Kapoor, Wishwa N.
Abstract Background Little is known about how investigators approach their research programs along the translational research continuum. Many consider the translational continuum to be linear, with research beginning at the bench and concluding with research at the bedside or in the community. We aimed to understand if translational investigators approach and view their research in this fashion. Methods We conducted semistructured individual interviews with 16 graduates of the University of Pittsburgh's Multidisciplinary Clinical Research Scholars Program (KL2) in 2012. Results Our research revealed three characteristic models. The first model we called "linear" and represented the traditional approach. The second we called "holistic"; these investigators began with central research questions and sought to explore them in every direction of translation, not necessarily taking linear steps. The third model we called "technical"; in this model, investigators focused on a unique technology or methodology and applied it across multiple research contexts. Conclusion This study found that there are multiple ways that translational investigators approach their research program. Better understanding of these models can help educators and mentors guide investigators so that they can be more productive in their clinical or translational research career.